PENGEMBANGAN PANDUAN IDENTIFIKASI DAN ASESMEN SISWA BERKEBUTUHAN KHUSUS DI SDN INKLUSI X SURABAYA - Tyas Leylasari, Herdina (Widya Warta, 2015)
The aim of this research is to create the development on identification and assessment guides for students with special needs. This study is a development research. It comprises someprocesses or steps performed to develop a new product or to improve an existing product. The data were collected in two steps – assessment and intervention. The assessment was doneusing interviews, observations, and primary data; while, the intervention was conducted applying evaluation by experts and evaluation on questionnaires concerning the guide books.The participants involved in the assessment were the deputy of principal, the classroom teachers, and the special-classroom teachers. Those who were involved in the interventionwere the classroom teachers and the special-classroom teachers. The data analysis in the assessment made use of content analysis technique and the one in the intervention appliedpercentage calculation. The results of the assessment showed that the problems were less appropriate with the identification and assessment processes previously done; the maininfrastructure and the supporting one were not sufficient; the teachers' classroom management did not fit the standard; the teachers lacked competence; and, the curriculum was not suitable. Likewise, the results of the intervention indicated that the research product was quite helpful for the teachers both in learning-teaching processes and in handling the students with special needs.